Determination of ovulation time in sows based on skin temperature and genital electrical resistance changes. (1st June 2013) - Luño, V.; Gil, L.; Jerez, R. A.; Malo, C.; González, N.; Grandía, J.; de Blas, I.
Abstract : Different physical and physiological parameters may be used to determine ovulation time in sows. In the present study, we analysed the ear and vulvar skin temperature fluctuations, and the changes in genital electrical resistance, at a distance of 4, 8 and 12 cm from the vulva during oestrus in order to predict the time of ovulation. Multiparous sows were checked by transrectal real‐time ultrasonography and luteinising hormone (LH) plasma concentration was determined. Temperature was measured using a thermoprecision infrared thermometer, and the electrical resistance was measured with a commercial resistance probe. All measurements were carried out every 12 hours from one day after the weaning to three days after oestrus onset. Skin temperature showed significant difference around periovulatory period. The electrical resistance at 4 cm from the vulva showed marked changes during oestrus, which were different from those described at 8 and 12 cm from the vulva. At 12 hours before ovulation time, skin temperature decreased significantly, and negative correlation (P<0.05) was found between vulvar skin temperature and vaginal resistance. There was no relationship between skin temperature, electrical resistance and LH plasma concentration. The measurement of several physiological traits may provide more accurate predictions of the moment of ovulation.